2017
DOI: 10.1002/pssa.201700138
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric characterization based on a printable resonant stub in air and a liquid environment

Abstract: Phone: +33(0)169153775, Fax: +33 (0)1 69 15 40 50This paper develops a new approach for in situ characterization of specific dielectric-based products that are located in complex geometric containers. The method uses a resonant T-topology of microstrip lines realized on a flexible substrate. This narrowband interferometric technique consists of determining the dielectric properties via the resonance characteristics of a flexible band-stop filter. The system is designed for the application of RFID (Radio-Freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…One of the most significant current discussions in liquid detection using microwave resonator sensors is the binary mixture of two liquid materials. Some researchers tested various combinations of water-ethanol [11,54,55], water-acetone [56] and alcohol [57], while others tested different pure liquids such as water, ethanol, methanol [11,45,[54][55][56][57][58][59][60][61], acetone [56,60], petrol [62], isopropanol [60], benzene, ethyl acetate, hexane, pentane [63], chloroform [55,64], soya, lemon tea, Nescafe and Kickapoo [58]. Table 3 demonstrates various liquids' detection based on existing studies found in the literature.…”
Section: Detection Of Liquid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most significant current discussions in liquid detection using microwave resonator sensors is the binary mixture of two liquid materials. Some researchers tested various combinations of water-ethanol [11,54,55], water-acetone [56] and alcohol [57], while others tested different pure liquids such as water, ethanol, methanol [11,45,[54][55][56][57][58][59][60][61], acetone [56,60], petrol [62], isopropanol [60], benzene, ethyl acetate, hexane, pentane [63], chloroform [55,64], soya, lemon tea, Nescafe and Kickapoo [58]. Table 3 demonstrates various liquids' detection based on existing studies found in the literature.…”
Section: Detection Of Liquid Materialsmentioning
confidence: 99%
“…This review shows the recent development of various studies and examples of applications of microwave planar sensors in material characterization. It includes the mathematical models for complex permittivity extraction [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], sensing application examples of microwave sensors [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , …”
Section: Introductionmentioning
confidence: 99%
“…Complementary split-ring resonator (CSRR)-based sensors are one of the most widely used devices in several potential applications of microwave sensing, including the characterization of electromagnetic properties of materials, characterization of liquids, and, more particularly, biological material testing [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%